2013
DOI: 10.4028/www.scientific.net/amr.652-654.1106
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Growth Behavior of the Intermetallic Compound for Sn-1.0Ag-0.5Cu-NiB/Cu Solder Joint Interface

Abstract: This research investigates the microstructure and growth behavior of the intermetallic compound(IMC) of Sn-1.0Ag-0.5Cu,Sn-1.0Ag-0.5Cu-0.05Ni and Sn-1.0Ag-0.5Cu-0.05N-0.02B/Cu solder joint interface. The interfacial reactions between Cu and the solders at 250±1°C were examined. Experimental results indicated that the IMCs of the above alloy systems on the soldering interface were Cu6Sn5and (Cux, Ni1-x)6Sn5, respectively. The grain size of primary Sn decreased observably with the micro addition of B and a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…And the finer the grain size, the higher the strength and hardness of the solder alloys are [8].Furthermore, the analysis of shear strength for different components solder alloys also confirmed this. There are three kinds of interface intermetallic compounds in SAC105 series solder alloys: Ag 3 Sn, Cu 3 Sn and Cu 6 Sn 5 [10,11]. It can be observed two main intermetallic compounds in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…And the finer the grain size, the higher the strength and hardness of the solder alloys are [8].Furthermore, the analysis of shear strength for different components solder alloys also confirmed this. There are three kinds of interface intermetallic compounds in SAC105 series solder alloys: Ag 3 Sn, Cu 3 Sn and Cu 6 Sn 5 [10,11]. It can be observed two main intermetallic compounds in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Aging treatment method can quickly and effectively reflect the growth behavior of intermetallic compound, which is an effective method in examining the reliability of the new type of solder. Through analyzing the IMC layer thickness and shape of the samples, the influence of the trace element B on solders' reliability can be revealed [11,12]. In the process of aging, external heating atmosphere provide enough energy for mutual diffusion between Sn in solder and Cu in substrate, which makes the thickness and microstructure changed in solder joints.…”
Section: Iumrs International Conference In Asiamentioning
confidence: 99%
“…The presence of Ni may improve the wetting behavior of copper substrates by the solder [4]. Previous work indicated that adding a trace amount of B into Sn-Ag-Cu solder can visibly improve the mechanical properties and effectively refine the microstructure of the solder [5]. The study of the interfacial zone is important to explain the reactions that occur during the soldering process and the intermetallic compound(IMC) formed.…”
Section: Introductionmentioning
confidence: 99%